2022
DOI: 10.1103/physreva.105.022602
|View full text |Cite
|
Sign up to set email alerts
|

Magic state distillation from entangled states

Abstract: Magic can be distributed non-locally in many-body entangled states, such as the low energy states of condensed matter systems. Using the Bravyi-Kitaev magic state distillation protocol, we find that non-local magic is distillable and can improve the distillation outcome. We analyze a few explicit examples and show that spin squeezing can be used to convert non-distillable states into distillable ones. Our analysis also suggests that the conventional product input states assumed by magic distillation protocols … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 61 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…In particular, it has been reported that the phase-GHZ state with a 𝜋/4 phase can be useful for magic-state distillation. [30] We can prepare the desired phase-GHZ state |PGHZ (4) (𝜃)⟩ with phase 𝜃 by adjusting the local phase of one of the four photons. In this procedure, |PGHZ (4) (𝜃)⟩ can be expressed as the unitary transformation of the |GHZ (4) ⟩ state, with the zero-phase expressed in Equation (3), as follows:…”
Section: Four-photon Ghz State With a Phase From A Warm Atomic Ensemblementioning
confidence: 99%
See 2 more Smart Citations
“…In particular, it has been reported that the phase-GHZ state with a 𝜋/4 phase can be useful for magic-state distillation. [30] We can prepare the desired phase-GHZ state |PGHZ (4) (𝜃)⟩ with phase 𝜃 by adjusting the local phase of one of the four photons. In this procedure, |PGHZ (4) (𝜃)⟩ can be expressed as the unitary transformation of the |GHZ (4) ⟩ state, with the zero-phase expressed in Equation (3), as follows:…”
Section: Four-photon Ghz State With a Phase From A Warm Atomic Ensemblementioning
confidence: 99%
“…In particular, it has been reported that the phase‐GHZ state with a π/4 phase can be useful for magic‐state distillation. [ 30 ] We can prepare the desired phase‐GHZ state |PGHZ(4)false(θfalse)$| {PGH{Z}^{(4)}(\theta )} \rangle $ with phase θ by adjusting the local phase of one of the four photons. In this procedure, |PGHZ(4)false(θfalse)$| {PGH{Z}^{(4)}(\theta )} \rangle $ can be expressed as the unitary transformation of the |GHZ(4)$| {GH{Z}^{(4)}} \rangle $ state, with the zero‐phase expressed in Equation (3), as follows: PGHZ(4)false(θfalse)=Ufalse(θfalse)GHZ(4)=normalI1normalI2normalI3()|〉H〈|H+eiθ|〉V〈|V4GHZ(4)=12|〉HHHH+eiθ|〉VVVV,$$\begin{equation} \def\eqcellsep{&}\begin{array}{l} \left| {PGH{Z}^{(4)}(\theta )} \right\rangle = U(\theta )\left| {GH{Z}^{(4)}} \right\rangle \\ \quad = \left[ {{{\mathrm{I}}}_1 \oti...…”
Section: Four‐photon Ghz State With a Phase From A Warm Atomic Ensemblementioning
confidence: 99%
See 1 more Smart Citation